LAW ENFORCEMENT ON UNDER AGE OF CRIMINAL WHICH ABUSE DRY MARIJUANA TYPES OF NARCOTICS - Liya, R R; Agung Fazri, Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2021)
The involvement of children in the world of narcotics cannot be separated from parental control, because parents must protect, educate and provide a decent life both physically and psychologically. Parents are expected to supervise and educate their children to stay away from narcotics abuse. By providing religious education and general education. The young generation is the backbone of the nation and the State, so that children, even though they have to face the law, must still receive protection. In writing this thesis the author provides an example of a case of a child who abuses narcotics and has been sentenced to imprisonment by a judge at the Pekanbaru High Court with his decision Number 68 / PID.SUS / 2013 / PTR. The formulation of the problems discussed by the author are: (1) How is law enforcement against offenders of minors who abuse narcotics? and (2) How is the application of material law to children as narcotics abusers as in Court Decision Number: 68 / PID.SUS / 2013 / PTR? The research method used by the author is a normative juridical method, which is to analyze the relationship between applicable laws and regulations with legal theories and the practice of implementing positive law concerning the issues discussed. Finally, the authors conclude that the application of material law to children as narcotics abusers as in Court Decision Number: 68 / PID.SUS / 2013 / PTR, turns out that there are differences in interpretation and differences in considerations so that there are differences in the provision of criminal sanctions against the accused. The District Court Judge sentenced a prison sentence of 1 (one) year, while the High Court judge imposed a heavier sanction of 2 (two) years and 6 (six) months imprisonment, which in the end had to be served, because this case only reached the appeal level in court High.